La historische Besinnung del vero essere. L’attualità della teleologia fenomenologica di Husserl - Ghigi, Nicoletta (Bollettino Filosofico, 2024)
Human reason, according to Husserl, is guided by a telos, by an entelechy that aims at the progress of human reason itself and that unfolds in history. But if this path is diverted or interrupted by a false entelechy, then teleology loses its goal and the telos reverses course towards a “decadent technique” in which the “foundations” and the “sense of reason” are lost and “forgotten”. It is the philosophers who have the task of reactivating the original teleology and bringing it back into evidence, through a historical awareness of the telos that constantly manifests itself in history. Keywords: Entelechy, Historische Besinnung, Reason, Teleology, Zweckidee